Experiences of work for people living with a grade 2/3 oligodendroglioma: a qualitative analysis within the Ways Ahead study - Walker, Hayley; Rimmer, Ben; Dutton, Lizzie; Finch, Tracy; Gallagher, Pamela; Lewis, Joanne; Burns, Richéal; Araújo-Soares, Vera; Williams, Sophie; Sharp, Linda (BMJ open, 2023)
Objectives  This study aimed to explore the work experiences of people living with an oligodendroglioma. Design  This was a descriptive qualitative study. One- time semi-structured interviews exploring supportive care needs were conducted; work was discussed at various points throughout each interview. An inductive thematic analysis was undertaken. Setting  Participants were recruited across the UK through four National Health Service hospitals and the Brain Tumour Charity research involvement networks. Participants  19 people with grade 2 or 3 oligodendroglioma (mean age 52 years; male n=11). At diagnosis, 16 participants were working, 2 studying and 1 retired. At the interview (mean time since diagnosis 9.6 years; range 1-18 years), seven participants were working, eight retired (four on medical grounds) and four unable to work due to illness. - Results  Seven themes were constructed: (1) physical and cognitive limitations; (2) work ability and productivity; (3) work accommodations; (4) changing roles; (5) attitudes of clients and coworkers; (6) feelings and ambitions; and (7) financial implications. Fatigue, seizures and cognitive deficits influenced work ability. A stressful work environment could exacerbate symptoms. Changes in job roles and work environment were often required. Employer and coworker support were integral to positive experiences. Work changes could result in financial stress and strain. - Conclusions  This study has highlighted, for the first time, influences on work experiences in this understudied population. These findings have implications for clinicians and employers, when considering the importance of work in rehabilitation for people with oligodendrogliomas, and the individually assessed adjustments required to accommodate them, should employment be desired.